Laser stimulated optical features of gold nanoparticles attached on ITO substrate. - Aziz, M.A.; Oyama, Munetaka; Ali Hussain, Reshak, Prof. Dr.; Gondek, Ewa; Armatys, Paweł; Shebl, Ahmed M.; Kityk, Ivan V.; Wojciechowski, Artur; Otowski, Wojciech (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/